Inorganic hole transporting materials towards stable perovskite solar cells - Zhao, Anqi (2015)
Organic lead halide perovskite solar cells have attracted extensive attentions and emerged as one of the most promising candidates for the future generation of solar cells. However, commonly employed organic hole transport materials in perovskite based solar cells are expensive and have low hole mobility. Meanwhile, current research mainly focuses on photo current conversion efficiency, and the stability of perovskite solar cells hasn’t been widely addressed. In order to explore a substituent for the conventional organic hole transport material, we have identified P3HT functionalized carbon nanotube as a possible alternative. By embedding the P3HT@SWNT hybrid material in polymethyl methacrylate (PMMA) matrix, we have achieved an impressive power conversion efficiency of 8.7%, which is comparable to the champion cell of spiro-OMeTAD made from the same under-stacking structure. It also shows higher incident photon to current conversion efficiency at wavelength above 500 nm. Meanwhile, the devices exhibited excellent stability under both heat and moisture attack condition showing no degradation of devices’ performance compared with significant degradation of spiro-OMeTAD and P3HT cells. By reducing the loss of functionalized SWNT during washing procedure, it is possible to mass-produce the perovskite solar cells using P3HT@SWNT as an effective hole transport material.